Analisis Penerapan Layanan Publik dalam Rangka Meningkatkan Kualitas Layanan Keagamaan pada Kantor Kementerian Agama Kabupaten Tabanan - Dwi Wahyudi, I Nengah Nirmala (JURNAL ILMIAH GEMA PERENCANA, 2023)
This article describes issue of religious services as one type of public service that aims to meet public needs for quality services that are easily accessible to the public. The office of the Ministry of Religion of Tabanan Regency is the service provider as mandated by UU No. 25 Year 2009 and PMA No. 65 Year 2016. Service delivery is carried out through the One Stop Integrated Service (PTSP). PTSP services have not been able to provide quality services according to community needs. Providing quality public services requires a strategy that makes it easier for the public to access and know the types of services being provided. In identifying strategies it is analyzed through the Customer Relationship Management (CRM) approach and Porter's Competitiveness Diamond Model (PCDM) to analyze the level of service competitiveness and in analyzing strategies using SWOT by selecting one of several alternative strategies available using the IFAS and EFAS methods. Keywords: Public Service, Excelent Services, CRM, PCDM, SWOT.